A Semantic-Based Software Architecture for Processing Context Information in Ubiquitous Medicine - Rodrigues, Sérgio; Dilli, Renato; Costa, Cristiano; Barbosa, Jorge; Venecian, Luthiano; Yamin, Adenauer; Lopes, João; Souza, Rodrigo; Geyer, Cláudio (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2011: Anais do XII Simpósio em Sistemas Computacionais de Alto Desempenho, 2011)
Ubiquitous medicine aims to provide healthcare services at any time, without restriction of location, enhancing the mobility of health professionals. Considering this premise, in this paper we propose a software architecture model that integrates sensors and computing devices (mobile or fixed) in a ubiquitous environment, providing context-awareness service. This model, called uMED, uses semantic processing technologies in the contextual information acquisition and processing. To evaluate the uMED, we present a case study related to clinical monitoring of patients.